Monitoring genetske pestrosti gozdov - Westergren, Marjana (Gozdarski vestnik, 2011)
Changes of environmental conditions and silvicultural practices strongly affect evolutionary forces, leading to changes in the patterns of genetic diversity. To assist conservation and management of genetic diversity of forest tree populations, thus enabling continuous adaptability of forest tree populations to future environments, it is becoming increasingly important to monitor consequences of environmental changes and intended or unintended anthropogenic influences on populations. Genetic monitoring, also mentioned instrategic European and national documents, is a system that enables quantification of temporal changes in population genetic matrices or other population data. Its main objective is to answer the question whether populations can ensure sustainable development of the existing forest. Development of genetic monitoring system must include a definition of a robustas well as labour and financially feasible sampling and experimental design.
Keywords: gozdovi; genetska pestrost; populacije; sistem vzorčenja